A research on the Gaziantep chukar production station - Bal, Gökhan (Bursa Technical University, 2024)
Chukar (Alectoris chukar) is one of the most popular game birds in Türkiye. The generation of this species has been dramatically reduced in the last century. It is possible to reproduce this bird species, bring it to nature, develop hunting tourism in our country, make particular hunting areas and earn income from hunting tourism. Chukar (Alectoris chukar) is found over large areas in Türkiye and over the world. Unfortunately, their population has been decreasing due to human pressure in the country. Breeding stations have been established to produce of this species in Türkiye in order to increase their population and make them available for hunting. The breeding stations are the areas where the extinct species are artificially produced, and the facilities required for production are established. Their primary purpose is to produce extensively species in artificially established facilities, place these animals in suitable habitats or new production stations, and benefit from animals placed in production stations as new breed-ing stations. Although chukar breeding is just a hobby for some people in Türkiye, it has been made by some gov-ernment agencies and research purposes in Faculties of Agriculture and Veterinary in some universities to ensure the continuation of his generation in recent years. In this study, located in Gaziantep province, studies were carried out on the producing and releasing wild animals to nature at the production stations. General information were given about the establishment of production stations, production techniques, working order, encountered problems, appli-cations to solve problems, and precautions. A detailed investigation and research have been carried out on the Chukar Production Station established in Gaziantep province. In this context, Gaziantep Chukar Production Station is located at the provincial borders. After the hunting and wild animals are produced in this station, they are placed in nature in the docking sites. In this study, deficiencies and problems of the production station mentioned above have been revealed.

Kınalı keklik (Alectoris chukar), Türkiye'deki en popüler av kuşlarından biridir. Bu türün nesli son yüzyılda önemli ölçüde azalmıştır. Bu kuş türünü çoğaltmak, doğaya bırakmak, ülkemizde av turizmini geliştirmek, belirli av alan-ları oluşturmak ve av turizminden gelir elde etmek mümkündür. Kınalı keklik (Alectoris chukar), Türkiye'de ve dünyada geniş alanlarda bulunur. Ne yazık ki, ülke genelinde insan baskısı nedeniyle nüfusları azalıyor. Bu türün popülasyonunu artırmak ve avlanmaya uygun hale getirmek amacıyla Türkiye'de üretim istasyonları kurulmuştur. Üretim istasyonları nesli azalan türlerin yapay olarak üretildiği ve üretim için gerekli tesislerin kurulduğu alanlardır. Başlıca amaçları, yapay olarak kurulan tesislerde türleri yaygın olarak üretmek, bu hayvanları uygun habitatlara veya yeni üretim istasyonlarına yerleştirmek ve üretim istasyonlarına yerleştirilen hayvanlardan damızlık olarak faydalanmaktır. Türkiye'de bazı insanlar için keklik yetiştiriciliği sadece bir hobi olmasına rağmen, son yıllarda neslinin devamını sağlamak için bazı devlet kurumları ve üniversitelerin Ziraat ve Veteriner Fakültelerinde araştır-ma amaçlı olarak yapılmaktadır. Bu çalışmada, Gaziantep ilinde bulunan üretim istasyonlarında yaban hayvan-larının üretimi ve doğaya bırakılması üzerine çalışmalar yapılmıştır. Üretim istasyonlarının kurulumu, üretim teknikleri, çalışma düzeni, karşılaşılan sorunlar, sorunları çözme uygulamaları ve alınan önlemler hakkında genel bilgiler verilmiştir. Gaziantep ilinde kurulan Kınalı Keklik Üretim İstasyonu hakkında ayrıntılı bir inceleme ve araştırma yapılmıştır. Bu bağlamda, Gaziantep Erikçe Kınalı Keklik Üretim İstasyonu il sınırları içinde yer almak-tadır. Bu istasyonda av ve yaban hayvanları üretildikten sonra, yerleştirme alanlarında doğaya bırakılırlar. Bu çalışmada, yukarıda bahsedilen üretim istasyonunun eksiklikleri ve sorunları ortaya konmuştur.
Gaziantep kınalı keklik üretim istasyonu üzerine araştırmalar
Keywords: Forest Entomology and Forest Protection; Orman Entomolojisi ve Orman Koruma